PENCEGAHAN PENYAKIT MENULAR DI BARENGKRAJAN, KABUPATEN SIDOARJO MELALUI PENINGKATAN KETERAMPILAN HIGIENE DAN SANITASI DEPOT AIR - Marlik Marlik; Iva Rustanti Eri Wardoyo; Demes Nurmayanti; Ferry Kriswandana (LPPM Universitas Abdurrab, 2025)
The quality of safe drinking water is crucial for preventing waterborne diseases; however, most Refillable Drinking Water Depots (DAM) in Barengkrajan Village, Krian District, Sidoarjo Regency do not meet sanitation standards and lack health eligibility certificates, posing risks of diarrhea and typhoid. A community service program was conducted to improve the knowledge and skills of 60 owners and staff from 9 DAMs regarding facility maintenance, personal higiene, water sampling, and sanitation in accordance with Ministry of Health Regulation No. 2 of 2023. The activities included training sessions, workshops, field assistance, and pretest-posttest evaluations, followed by monitoring and coaching. The evaluation results showed an increase in participants’ average knowledge scores from 41.2 to 77.7 points, along with improved higiene practices, use of personal protective equipment (PPE), and regular maintenance. This program demonstrates that community-based educational approaches are effective in enhancing DAM management quality and supporting the SDGs related to safe drinking water access.